(untitled) (Bangladesh Veterinarian, 2013)
A partial diallel crossing of Rhode Island Red (RIR), White Leghorn (WLH), Fayoumi (FO), Desi normal (DN) and Desi dwarf (DD) produced RIR, WLH, FO, DN, DD, RIR x DD, WLH x DD and FO x DD offspring. A total 709 chicks, 75 RIR, 130 WLH, 100 FO, 70 DN, 66 DD, 80 RIR x DD, 80 WLH x DD and 108 FO x DD were reared for studying growth performance up to 18 weeks of age. At 19 weeks, the crossbreds RIR x DD, WLH x DD and FO x DD were separated into normal and dwarf genetic groups on the basis of shank length and thus 11 genetic groups, RIR, WLH, FO, DN, DD, RIR x DD normal, RIR x DD dwarf, WLH x DD normal, WLH x DD dwarf, FO x DD normal and FO x DD dwarf were obtained. Day-old weight differed significantly (P<0.05) between genotypes. When crossed with Desi dwarf, the day-old weight of RIR, WLH and FO decreased by 7.0, 8.7 and 15.3%. DD chicks had 9.2% lower day-old weight than DN. All DD and DD crossbred chicks had lower feed intake (P<0.01) at all stages of growth. There were no significant differences in daily weight gain, feed conversion ratio and mortality between genotypes (P>0.05). The shank length differed significantly between genotypes at all ages regardless of sex (P<0.01) and differences between genotypes increased at older ages. Shank length of pure breeds and normal crossbreds were similar and much longer than in dwarf crossbreds DOI: http://dx.doi.org/10.3329/bvet.v30i1.16282 Bangl. vet. 2013. Vol. 30, No. 1, 25-32